A Collaborative Curriculum Review Process: Applicability to Higher Education Institutions. - Egwar, Andrew Alunyu; Bwire, Felix; Arinaitwe, Irene; Male, Vincent; Mpirirwe, Hilda; Baguma, Kenneth; Kamukama, Ismail; Ndagire, Lillian; Nabukenya, Josephine (Proceedings of the 51st Hawaii International Conference on System Sciences, 2018)
Curriculum review is mandatory for all higher education institutions (HEIs). The process brings together different stakeholders’ expertise to evaluate and revise an existing curriculum, positioning the field of study within the current market and industry trends. Although this process is repetitive, it still remains complex, majorly due to divergent stakeholders’ interests, varying levels of expertise, uncertain activity paths and multiple desired outcomes. The paper thus presents a Collaborative Curriculum Review Process (ColCuRP) to support the review of varying curricula in HEIs. We followed a mixed research approach (design science and action research) to design and evaluate the ColCuRP. It underwent four iterations during its evaluation and proved to be successful regards reduction in time for the review process, and supporting the different teams of departmental faculty to review Bachelors, Post Graduate Diploma, Masters and PhD curricula, at four HEIs in Uganda. Moreover, the ColCuRP can be used by inexperienced facilitators.
Keywords: Higher Education Institutions (HEIs).; Curriculum